Comparison of outcomes of open hernioplasty- Lichtenstein versus laparoscopic trans abdominal preperitoneal mesh repair in patients with uncomplicated unilateral inguinal hernias - S., Elakkiya; T., Deepu (International Surgery Journal, 2019)
Background: Inguinal mesh hernioplasty is one of the common procedures performed throughout the world. There are open and laparoscopic techniques of hernia repair. The laparoscopic approach to inguinal hernioplasty is now well established. The purpose of this study was to compare the outcomes of Lichtenstein tension free hernioplasty and laparoscopic TAPP (transabdominal preperitoneal mesh repair) considering these criterias, such as, duration of the surgery, hospital stay, and duration to resume normal activity, cosmesis, degree of postoperative pain, wound infection, recurrence and complications. Methods: A prospective randomized study was conducted by comparing patients (two groups) who underwent laparoscopic (TAPP) and Lichtenstein Tension free open hernioplasty in SVMCH and RC from November 2016 to June 2017. Results: Among the two groups of patients, depending on my criteria’s, namely, cosmesis (p-0.074) and postoperative cord edema (p-0.042), patients who underwent TAPP had statistically better outcomes than open hernioplasty. Conclusions: My study concludes that laparoscopic TAPP repair is safe and efficacious and the analysis here states the absolute superiority of laparoscopic TAPP over Lichtenstein tension free hernioplasty.